2017
DOI: 10.1080/01635581.2017.1339816
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cytotoxic Activity of Crocin and Safranal, Constituents of Saffron, in Oral Squamous Cell Carcinoma (KB Cell Line)

Abstract: Crocin and safranal are active ingredients in the saffron. Some studies have demonstrated antitumor activities of saffron ingredients. The aim of this study was to evaluate cytotoxic effects of crocin and safranal in oral squamous cell carcinoma (KB cells) and NIH 3T3 cell line as nonmalignant cells. The cells were incubated with crocin and safranal at 37°C for 24, 48, and 72 h, and cell viability was quantitated by MTT assay. Apoptotic cells, cell cycle distribution, and sub-G1 fraction were determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…On treatment with safranal and crocin, the cells exhibited a dose-dependent cell viability inhibition pattern, similar to saffron (Figures 3 and 4). Safranal and crocin dose ranges in our study are close to the effective doses published for other cancers [9,18,19]. Malaekeh-Nikouei et al have reported safranal's effective dose range to be much higher for other cells suggesting that HCT116 cells have a higher susceptibility [20].…”
Section: Discussionsupporting
confidence: 86%
“…On treatment with safranal and crocin, the cells exhibited a dose-dependent cell viability inhibition pattern, similar to saffron (Figures 3 and 4). Safranal and crocin dose ranges in our study are close to the effective doses published for other cancers [9,18,19]. Malaekeh-Nikouei et al have reported safranal's effective dose range to be much higher for other cells suggesting that HCT116 cells have a higher susceptibility [20].…”
Section: Discussionsupporting
confidence: 86%
“…Hence, gene expression was examined for BAX ( Figure 6 A), BID ( Figure 6 B), BCL2 ( Figure 6 C), MYCN ( Figure 6 D), SOD1 ( Figure 6 E) and GSTM1 ( Figure 6 F) when cells were treated with 1 mg/mL CRCs and DMCRT. Although it is well established that exposure of cancer cells to concentrations of saffron or its compounds up to 16 mg/mL are related to apoptotic cell death and not necrosis, via alterations in the expression of relevant apoptotic genes, the dose treatment of 1 mg/mL was selected, based on the significant cytotoxic effects observed on both cell lines, without however complete cellular abolishment or exceeding the IC 50 concentration for 48 and 72 h [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant effect of Safranal has been proposed as a possible mechanism for its anticancer activity. Cytotoxic activities of different safranal concentrations (0.2–3.2 mM) were tested on oral squamous cell carcinoma (KB) and NIH 3T3 as nonmalignant cell lines using MTT assay ( Jabini et al., 2017 ). This study demonstrated that safranal has >50% cytotoxicity on KB cells at 0.2 mM while showed <50% cytotoxic activity on normal cells (NIH 3T3 cells) at the same concentration after 72 hrs.…”
Section: Safranal In Cancermentioning
confidence: 99%